Konsep Rezeki Perspektif Wahbah al-Zuhaili Dalam Tafsir al-Munir - jatim mistar (STIU Al-Mujtama Pamekasan, 2020)
One of the enhancers of life for human being is fulfillment of sustenance. So that the sustenances became the main goal of human to survive their life. Reality that occurs when this, humans assume that the size of the provision is only found in the treasures of wealth alone. However, sustenance is actually divided into two. First, the provision that the requirement of physical like, food, drinks, clothing, house and others. Second, the provision which became needs spiritual as, science knowledge, intelligence, guidance in life. This research used qualitative approach with the type of library research, that is focused on the literary research which the materials relates to the theme of the study, then the data are analyzed by descriptive analysis. The results of research on the interpretation of Wahbah al-Zuhaili surah Hud verse 6, it can be concluded that every human being is guaranteed the welfare of his sustenance, even all creatures on earth even though they have their own sustenance. Further, Wahbah Zuhaili emphasized that sustenance will be guaranteed if humans are willing to try and work in accordance with the human rights in living this life. Keywords: Concept, blessing, interpretation, Wahbah al-Zuhaili